Diagnostic Accuracy of Screening Mammography in Detection of Breast Neoplastic Lesion Taking Histopathology as a Gold Standard - Rao, Hina Akber; Shaukat, Shaista; Shahbaz, Sumaira; Mahmood T.I, Tariq; Akbar, Asifa; Akber, Maryiam (Biological and Clinical Sciences Research Journal, 2025)
Breast cancer remains the most frequently diagnosed malignancy among women worldwide, where timely and accurate detection is critical for improving survival outcomes. Mammography has long been considered the cornerstone of screening programs; however, its diagnostic performance varies with population characteristics and breast density, necessitating validation against histopathology, the gold standard for diagnosis. Objective: This study aims to evaluate the diagnostic accuracy of screening mammography in detecting breast neoplastic lesions by comparing it to histopathological results, while also assessing the impact of key clinical variables on diagnostic outcomes. Methods: After obtaining ethical approval from the institutional review board, this cross-sectional study was conducted at the Radiology department of JPMC from January 1, 2023, to June 30, 2023. Through non-probability consecutive sampling, 100 patients, aged 30 years and above, who had undergone both mammography and histopathological biopsy (core needle or excisional) for suspected breast lesions. Only cases with complete clinical records, including imaging findings, histopathology results, and relevant clinical history, were selected. Patients with incomplete records, previous diagnoses of breast cancer, or those undergoing follow-up for known malignancies were excluded. Results: The calculated sensitivity of screening mammography was 88.68%, indicating its high ability to identify patients with breast neoplastic lesions accurately. The specificity was 82.89%, reflecting its accuracy in ruling out disease in non-affected individuals. The positive predictive value (PPV) stood at 85.45%, while the negative predictive value (NPV) was 86.67%. The overall diagnostic accuracy of mammography in this study was 86.00%. Furthermore, Receiver Operating Characteristic (ROC) curve analysis was performed to evaluate the diagnostic performance of mammography. The curve demonstrated a high area under the curve (AUC = 0.728), supporting the reliability of mammography as a screening tool for breast cancer. Conclusion: Screening mammography, when benchmarked against histopathology, demonstrates high overall accuracy—with sensitivity and specificity exceeding 80%—affirming its reliability for early breast cancer detection while underscoring the importance of density-adapted, patient-tailored screening protocols.